PS02.011: ESOPHAGECTOMY IN A LOW VOLUME SINGLE CENTER FAVORING A TOTAL MINIMALLY INVASIVE APPROACH: 55 PATIENTS IN 7 YEAR. (14th September 2018) - Gehwolf, Philipp; Schmid, Thomas; Öfner-Velano, Dietmar; Wykypiel, Heinz
Abstract: Background: In Austria esophageal cancer is not very common. The incidence is 8.8/100.000 per year, thus esophageal cancer is on rank 18 of the most common carcinomas. Multimodal treatment inclouding surgery is standard for locally advanced esophageal cancer with a 5-year survival rate of around 40% in patients treated with a curative intent. Methods: Retrospective single institution study in a tertiary care center using prospectively collected data we discuss our surgical procedure with patient survival as primary endpoint and morbidity as secondary endpoint. Results: From 2010–1017, 55 Patients received an esophageal resection. The mean age was 61.5 years, five patients (9%) were female. Squamous cell carcinoma appeared in 37%, adenocarcinoma in 59% and a verrucous carcinoma in 4% of our patients. 98% of patients received an esophagectomy with gastric tube pull up, in 2% the colon was used for reconstruction. For patients with carcinoma located in the lower and middle thoracic esophagus a thoracic anastomosis was targeted (78%), in carcinomas of the upper thoracic esophagus a left cervical anastomosis (22%) was performed. Depending on location and comorbidities patients received either a conventional operation (11%), a hybrid operation with laparotomy and thoracoscopic esophageal resection (59%) or a totally minimal invasive approach (30%). The 60 days mortality was < 2%, the need for reoperation < 10%. Major complications (Clavien-Dindo III-V) were observed in 30%. Conclusion: Esophagectomy is a high-risk operation with serious mortality and morbidity. However, patients may profit from a tailored approach with intent for the minimally invasive approach even in a low volume center when expertise in high-end endoscopic surgery is available. Disclosure: All authors have declared no conflicts of interest.